Endocannabinoid-dependent plasticity at spinal nociceptor synapses - Kato, Ako (Blackwell Science Inc, 2012)
Neuroplastic changes at the spinal synapses between primary nociceptors and second order dorsal horn neurons play key roles in pain and analgesia. NMDA receptor-dependent forms of long-term plasticity have been studied extensively at these synapses, but little is known about possible contributions of the endocannabinoid system. Here, we addressed the role of cannabinoid (CB)(1) receptors in activity-dependent plasticity at these synapses. We report that conditional low-frequency stimulation of high-threshold primary sensory nerve fibres paired with depolarisation of the postsynaptic neuron evoked robust long-term depression (LTD) of excitatory synaptic transmission by about 40% in the vast majority (90%) of recordings made in wild-type mice. When recordings were made from global or nociceptor-specific CB(1) receptor-deficient mice (CB(1)(−/−) mice and sns-CB(1)(−/−) mice), the portion of neurons exhibiting LTD was strongly reduced to about 25%. Accordingly, LTD was prevented to a similar extent by the CB(1) receptor antagonist AM 251 and mimicked by pharmacological activation of CB(1) receptors. In a subset of neurons with EPSCs of particularly high stimulation thresholds, we furthermore found that the absence of CB(1) receptors in CB(1)(−/−) and sns-CB(1)(−/−) mice converted the response to the paired conditioning stimulation protocol from LTD to long-term potentiation (LTP). Our results identify CB(1) receptor-dependent LTD as a form of synaptic plasticity previously unknown in spinal nociceptors. They furthermore suggest that prevention of LTP may be a second hitherto unknown function of CB(1) receptors in primary nociceptors. Both findings may have important implications for our understanding of endogenous pain control mechanisms and of analgesia evoked by cannabinoid receptor agonists.